2022
DOI: 10.3389/fanim.2021.785253
|View full text |Cite
|
Sign up to set email alerts
|

Use of Beef Semen on Dairy Farms: A Cross-Sectional Study on Attitudes of Farmer Toward Breeding Strategies

Abstract: The use of beef semen on dairy cows has been increasing steadily since 2017. We aimed to describe dairy management practices toward the use of beef semen by surveying farmers in California, the largest US dairy producer. In January 2020, we mailed a printed version of the beef semen use survey to 1,017 dairy producers in California, who also had the option to answer the survey online. The questionnaire consisted of 33 questions that were categorized into three sections: general herd information (n = 10), beef … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Of the respondents using beef semen, 88.2% declared making an additional profit due to incorporating beef semen in their breeding decisions. Unlike the profitability reported by Pereira et al (2022) , where Angus cross progeny profitability was more variable than other breeds, profitability of beef × dairy crosses, within the Northeast survey respondents, was less dependent on breed. In fact, reported profitability was variable and, thus, it was difficult to ascertain the primary driver of profit.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Of the respondents using beef semen, 88.2% declared making an additional profit due to incorporating beef semen in their breeding decisions. Unlike the profitability reported by Pereira et al (2022) , where Angus cross progeny profitability was more variable than other breeds, profitability of beef × dairy crosses, within the Northeast survey respondents, was less dependent on breed. In fact, reported profitability was variable and, thus, it was difficult to ascertain the primary driver of profit.…”
Section: Discussioncontrasting
confidence: 66%
“…Dairies have rapidly adopted breeding with beef semen. Pereira et al (2022) reported that 81% of the dairies surveyed in California were using beef semen in their dairy cows and 76.7% of the variation in day-old calf price was explained by dairies that had contracts with calf-ranches. While fewer respondents in the Northeast report using beef semen (76.4% compared with the 81% adoption in CA), an additional 4.7% of respondents reported they plan to use beef semen in future dairy breedings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the number of beef breeds represented between these sires was limited. McWhorter et al (2020) and Pereira et al (2022) demonstrated that, in U.S. beef × dairy crossbreeding systems, Angus was the predominant sire breed of choice. Compared to these studies, Halfman and Sterry (2019) reported a lesser percentage use of Angus (although it was still predominant) and a greater percentage of other breeds, including Simmental, Limousin, and their Angus-influenced composites.…”
Section: Discussionmentioning
confidence: 99%
“…Survey results and evaluations of dairy herd management records suggest that Angus is the primary sire breed used in U.S. beef × dairy inseminations ( McWhorter et al. 2020 ; Pereira et al., 2022 ; Felix et al., 2023 ; Lauber et al., 2023 ). This is reflected by the shift away from fed Holstein steers to black-hided beef × dairy animals reported in the most recent National Beef Quality Audit ( NBQA, 2016 , 2023 ).…”
Section: Introductionmentioning
confidence: 99%